(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Needless to say, everyone in our world aspires to prosperity, safety, development, pleasure, and contentment. No one wants to see any indication of risks, difficulties, problems, etc. To the best of their knowledge, skills, and ability, everyone strives to overcome any obstacles they may encounter, especially those that concern themselves and their loved ones. In addition, it has been observed that the odd events that are taking place make individuals feel helpless. In an instant, a person is destroyed and loses everything